Endoscopic and Pathologic Changes of the Upper Gastrointestinal Tract in Crohn's Disease. (3rd February 2014) - Sakuraba, Atsushi; Iwao, Yasushi; Matsuoka, Katsuyoshi; Naganuma, Makoto; Ogata, Haruhiko; Kanai, Takanori; Hibi, Toshifumi
Abstract : Background . Crohn's disease (CD) may involve any part of the gastrointestinal tract. We assessed the prevalence and features of upper gastrointestinal (UGI) lesions in CD. Methods . This was a retrospective study that included 138 CD patients that underwent esophagogastroduodenoscopy (EGD). The rate of Crohn's specific endoscopic lesions in the esophagus, stomach, and duodenum was assessed, and immunohistochemical analysis was performed. Changes in the UGI lesions were assessed in those who had two or more EGD. Results . Of 138 patients, 51.3% had Crohn's specific UGI lesions. The rates of Crohn's specific lesion in the esophagus, upper-to-middle stomach, lower stomach, duodenal bulb, and 2nd portion of the duodenum were 6.5%, 47.8%, 24.6%, 31.9%, and 18.1%, respectively. Granulomas were detected in 6.1%, 25.0%, and 11.4% in the upper-to-middle stomach, lower stomach, and duodenal bulb, respectively, but none in the esophagus and 2nd portion of the duodenum. Thirty-seven were analyzed for Helicobacter pylori and 4 were positive (10.8%). Improvements of UGI lesions were seen in 14 out of 49 (28.5%) and were unchanged in 59.2% and worsened in 12.2%. Conclusions . The prevalence of Crohn's specific UGI lesions was common in our case series, and immunohistochemical studies suggested that the majority was unrelated to Helicobacter pylori infection. Worsening of UGI lesions over the course was rare.